Análisis de la estructura neurótica obsesiva, trastornos relacionados y dirección de la cura - Astudillo Pizarro, Ronald Paúl (My University, 2021)
This essay aims to analyze the obsessive neurotic clinical structure in order to propose a possible cure from psychoanalysis, describing the characteristics of osbessive neurosis, identifying the related pathologies from the diagnostic manuals and conceptualizing the cure. This research work has a qualitative approach of descriptive type, with a methodology based on bibliographic review. People with obsessive structure have a fixation in the anal phase, in this psychosexual stage of childhood where poor sphincter control is related to shame, guilt, disgust and sadism. The obsessive neurosis is produced from a sexual traumatic event of childhood origin where the subject has an active participation. The features that differentiate obsessives are guilt, order, rationalization, doubt and love-hate ambivalence, in addition to obsessive reproaches and prohibitions. The symptomatology of obsessive-compulsive disorders and obsessive personality disorder have similarities with the characteristics of the obsessive structure. Psychoanalysis seeks subjective rectification based on transference, free association of ideas and floating attention that are the key to unveil the unconscious, without reaching a complete cure, seeking self-knowledge in analysis that is unique to each individual.
El presente ensayo tuvo como objetivo analizar la estructura clínica neurótica obsesiva para poder plantear una posible cura desde el psicoanálisis, Para ello es necesario en primera instancia describir los rasgos de la neurosis obsesiva, identificar las patologías relacionadas y posteriormente conceptualizar la cura. Este trabajo de investigación es de enfoque cualitativo de tipo descriptivo, con una metodología basada en la revisión bibliográfica. Las personas con estructura obsesiva tienen una fijación en la fase anal, en esta etapa psicosexual de la niñez donde el poco control de esfínteres es relacionado con la vergüenza, la culpa, el asco y el sadismo. La neurosis obsesiva se produce a partir de un evento traumático sexual de origen en la infancia donde el sujeto tiene una participación activa. Los rasgos que diferencian a los obsesivos son la culpa, el orden, la racionalización, la duda y la ambivalencia amor-odio, además de los reproches obsesivos y las prohibiciones. La sintomatología de los trastornos obsesivo compulsivo y el trastorno de personalidad obsesiva poseen similitud con las características de la estructura obsesiva. El psicoanálisis busca la rectificación subjetiva con base en la transferencia, asociación libre de ideas y la atención flotante que son la clave para develar lo inconsciente, sin llegar a una cura completa, buscando el autoconocimiento en análisis que es único para cada individuo.
Keywords: NEUROSIS OBSESIVA; PSICOANALISIS; CURA